Fenilpropanoides da Paspalum atratum - Pinto, Luciano da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This work describes the phytochemical study on ethanol extract from aerial parts of Paspalum atratum Swalen (Poaceae). The Paspalum genus is one of the most important grasses in Brazil and has characteristics compatible with its utilization in pastures for cattle. Phenylpropanoids were isolated by chromatographic methods (CC and HPLC) for the first time in this genus. These phenylpropanoids were identified as (R)-rosmarinic acid (RA, 1), 3-O-caffeoylquinic acid (2), phenylalanine (3), cis- and trans-3-O-coumaroylquinic acids (4 and 5), 5-O-caffeoylquinic acid (6, chlorogenic acid), 4-O-caffeoylquinic acid (7), and caffeic acid (8) by analyses of their MS, 1H and 13C NMR data, including COSY, HMBC, HSQC and DOSY, and comparison of these data with those reported in the literature for these type of compounds. The major compound isolated from the ethanol extract was RA (4.4%). It was used as standard for qualitative and quantitative analyses of extract. An efficient HPLC-DAD method for determination of RA in extract was established (r2 = 0.9979). The limit of detection (LOD) and limit of quantification (LOQ) were 4.00 and 12.13 μg/mL, respectively, and the validated range was 12.1-100.0 μg/mL. The intra-day and inter-day precisions of the method were evaluated by analyzing the blank solution spiked by RA. The standard deviation (SD) as evaluation parameter for the intra-day precision of peak area of target analyte was in the range of 1.57-2.06%. The inter-day precision (7 days) of the method was in the range of 0.54-1.69%. Satisfactory recovery (75-78%), evaluated by standard additions method, was achieved.

Este trabalho descreve o estudo fitoquímico do extrato etanólico de Paspalum atratum Swalen (Poaceae). O gênero Paspalum é o mais importante das gramíneas no Brasil e possui características compatíveis com a utilização no pastejo. Fenilpropanoides foram isolados por métodos cromatográficos (CC, CLAE) pela primeira vez neste gênero. Estes fenilpropanoides foram identificados como: (R)-ácido rosmarínico, (AR, 1), ácido 3-O-cafeoilquínico (2), fenilalanina (3), ácidos cis- e trans-coumaroilquínico (4 e 5), ácido 5-O-cafeoilquínico (6), ácido 4-O-cafeoilquínico (7) e ácido cafeico (8) pela análise de seus dados de EM, RMN de 1H e de 13C, incluindo COSY, HMBC, HSQC, TOCSY-1D e DOSY, e pela comparação destes dados com aqueles descritos na literatura para estas substâncias. A substância majoritária no extrato etanólico foi o AR (4,4%). Esta foi usada como padrão em análises qualitativas e quantitativas do extrato. Um método eficiente em CLAE-DAD para determinação de AR no extrato foi estabelecido (r2 = 0,9979). O limite de detecção (LD) e limite de quantificação (LQ) foram 4,00 e 12,13 μg/mL respectivamente, e a faixa de linearidade foi 12,1-100,0 μg/mL. As precisões intradia e interdia do método foram avaliadas pela análise das soluções de padrão AR. O desvio padrão da área do pico do analito foi utilizado como parâmetro de avaliação da precisão intradia, compreendendo o intervalo de 1,57-2,06%. A precisão interdia (7 dias) do método compreendeu o intervalo de 0,54-1,69%. A recuperação, avaliada pela adição do padrão AR, foi satisfatória (75-78%.
Keywords: Gramínea; Ressonancia magnetica nuclear; Analise de variancia; Pastagens; Cromatografia líquida de alta eficiência; Fenilalanina